Implementasi Government Public Relations : (Studi Deskriptif Kualitatif di Pusat Pelatihan dan Pendidikan Kementerian Pendidikan Kebudayaan Riset dan Teknologi) - Gilang Handoko; Tria Patrianti (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Lack of understanding of Government Public Relations function by the Education and Training Center The Ministry of Education, Research and Technology is an obstacle to the implementation in conveying information, policies, regulations and educating the public which is still not optimal. The lack of experts and limited human resources results in ineffective communication in conveying information which can cause misunderstandings and inappropriate information received by the public. This study aims to determine the activities, actions, and mechanisms of Government Public Relations of the Education and Training Center of the Ministry of Education, Culture, Research and Technology. The research theory in this study is the theory of implementation and Government Public Relations which consists of disseminating public information, policies, regulations and educating the public about laws and regulations. This research methodology.This research methodology uses a qualitative approach with descriptive methods with data collection techniques are in-depth interviews. The implementation of Government Public Relations carried out by the public relations of the Education and Training Center of the Ministry of Education, Research Culture and Technology consists of activities such as providing accurate information, socializing to the public about government policies, interacting with the public, holding press conferences, and building relationships with the media.press conferences, and building relationships with the media. Government Public Relations actions carried out such as preparing information materials, accommodating, processing messages and aspirations of the community, by involving several stakeholders so that the information received by the public in the form of news, narratives, photos and videos is accurate and reliable. The Government Public Relations mechanism uses good governance, namely, equality, supervision, law enforcement, , effectiveness, and responsiveness, efficiency, participation, accountability, foresight and transparency.